2020
DOI: 10.1002/bin.1755
|View full text |Cite
|
Sign up to set email alerts
|

Generality of the practical functional assessment and skill‐based treatment among individuals with autism and mental health disorders

Abstract: A practical functional assessment format was recently developed that informed a skill‐based treatment for the problem behavior of children diagnosed with autism spectrum disorder. Since its inception there have been multiple replications of the procedures; however, the comprehensive model has rarely been applied to populations with more complex comorbid disorders and severe problem behavior such as those diagnosed with anxiety or depression. We conducted the current study to systematically replicate the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Pairwise designs were included in 29.8% of the studies included in our review, which was a substantial increase compared with that reported by Beavers et al (7.0%) and Hanley et al (2.5%). Notably, we classified most interview‐informed synthesized contingency analyses (Hanley et al, 2014) and practical functional assessments (e.g., Coffey et al, 2021) as using a pairwise experimental design (see Jessel et al, 2016, for examples), and these accounted for some of the increase in the use of the pairwise design. Similar to previous reviews, 13.2% of studies in our review used a reversal design (12.0% in Beavers et al, 2013; 15.5% in Hanley et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Pairwise designs were included in 29.8% of the studies included in our review, which was a substantial increase compared with that reported by Beavers et al (7.0%) and Hanley et al (2.5%). Notably, we classified most interview‐informed synthesized contingency analyses (Hanley et al, 2014) and practical functional assessments (e.g., Coffey et al, 2021) as using a pairwise experimental design (see Jessel et al, 2016, for examples), and these accounted for some of the increase in the use of the pairwise design. Similar to previous reviews, 13.2% of studies in our review used a reversal design (12.0% in Beavers et al, 2013; 15.5% in Hanley et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Skyler had previously gone through a successful behavioral intervention for severe behavior (outside of the mealtime context) of which he maintained zero to low rates of throughout his day. The treatment, specifically a skill-based treatment (Coffey et al, 2021), continued to be in place throughout his school day.…”
Section: Historymentioning
confidence: 99%
“…Additionally, the reinforcement of cooperative behavior during the delay likely competes with co‐occurring problem behavior. The DDTT process generally involves the following: (a) teaching and reinforcing FCRs, (b) teaching and reinforcing tolerance responses (e.g., saying, “OK” following the implementer's denial statement), and (c) gradually introducing delays following tolerance responses (e.g., Coffey et al., 2021; Fiani & Jessel, 2022; Ghaemmaghami et al., 2016; Hanley et al., 2014). Linking back to the previous example about tangibly maintained problem behavior, the individual would come to learn that their FCRs for their iPad are occasionally honored right away by the implementer but, on other occasions, FCRs result in a delay before the iPad is delivered.…”
Section: Introductionmentioning
confidence: 99%